2014
DOI: 10.1037/a0036672
|View full text |Cite
|
Sign up to set email alerts
|

Observed parental responsiveness/warmth and children’s coping: Cross-sectional and prospective relations in a family depression preventive intervention.

Abstract: The current study examined concurrent and prospective relations between observed parenting behaviors and children’s coping strategies in the context of a preventive intervention designed to change both parenting and children’s use of secondary control coping. Questionnaires and direct observations were obtained from parents with a history of depression (N = 180) and their children (ages 9–15 years) at baseline, 6-month (after completion of the intervention), and 18-month follow-up assessments. Cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Prior studies in the setting of family focused interventions for depression have suggested that parents who are sensitive to and accepting of difficult emotions in their children may promote the development of the child’s emotion regulation and coping skills and be more likely to be viewed as a source of support during times of stress for the child [62]. Our findings suggest that similar targets (e.g.…”
Section: Discussionmentioning
confidence: 61%
“…Prior studies in the setting of family focused interventions for depression have suggested that parents who are sensitive to and accepting of difficult emotions in their children may promote the development of the child’s emotion regulation and coping skills and be more likely to be viewed as a source of support during times of stress for the child [62]. Our findings suggest that similar targets (e.g.…”
Section: Discussionmentioning
confidence: 61%
“…In the future, intervention efforts may benefit from specifically targeting secondary control coping in families, such as by teaching parents to use this form of coping, helping parents foster this form of coping in their children, and building parenting skills that support children’s coping. Such an approach has been used successfully in enhancing coping skills and parenting skills in parents with depression and their children (Compas et al, 2010; Compas et al, 2015; Watson et al, 2014). This model holds promise for interventions for children with cancer and their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Results of parenting interventions (usually with mothers) in the United States and Europe have demonstrated that improving parenting behaviors can have positive effects on later child adjustment (Guttentag et al, 2014; Hanisch, Hautmann, Plück, Eichelberger, & Döpfner, 2014; Landry, Smith, Swank, & Guttentag, 2008; Watson et al, 2014). The results of this study suggest that parenting interventions with mothers and fathers may have similar effects on child adjustment in Western and non-Western countries.…”
Section: Discussionmentioning
confidence: 99%